SAS Combat Handbook - Davies, T. Barry (Skyhorse Publishing, 2015)
An SAS soldier explains the battle history of this prestigious military service, while teaching how you can defend yourself in both hand-to-hand and military combat. Seventy years after its inception, the Special Air Service (SAS) is recognized by many as one of the most decorated military forces in the world. Their soldiers do battle on a daily basis, taking actions that are normally swift, very hard hitting, and extremely secretive. They will go--willingly--deep behind enemy lines, taking on incredible odds and risking their lives in the hope of rescuing others. In the SAS Combat Handbook, you will be informed on all aspects of SAS operations. With never-before-seen photographs of these heroes in action and untold stories of individual acts of bravery, you will be taught the key combat methods that have made this military group exactly what they are: elite